Experimental study on the mechanical properties of corroded concrete pipes subjected to diametral compression. (20th November 2020) - Fang, Hongyuan; Yang, Kangjian; Du, Xueming; Li, Bin; Zhang, Xijun; Tan, Peiling
Highlights: The failure process and morphology of the corroded concrete pipes were investigated. Capacity and circumferential strains of corroded concrete pipes were analyzed. Considering various loading speeds, corrosion depths, corrosion widths and corrosion. Failure of concrete pipes have cracks appearance, cracks propagation and damage. Abstract: Corrosion commonly affects buried concrete drainage pipelines, causing pipe leaks, pipe explosions and even road collapses. To assess the mechanical properties of corroded concrete pipes, a series of pipeline mechanical performance test were performed. The failure process, carrying capacity and circumferential strains of corroded concrete pipes were analyzed under various loading speeds, corrosion depths, corrosion widths and corrosion locations. The results showed that cracks first appeared on the inside of the pipe crown and pipe invert, and as the load continued to increase, the cracks rapidly expanded. When cracks penetrated the entire section of the pipe, the pipe was crushed. The deformation of the pipe was small, and there was no plastic development stage in the pipe failure process, indicating that the concrete pipe exhibited brittle failure. The loading speed had a small effect on the carrying capacity of the pipe and a large effect on the circumferential strain of the pipe. Corrosion had a greater impact on the stress and strain in the corroded area of the pipe and a smaller impact on other locations. With increasing corrosion depth and corrosion width, the carrying capacity of the pipe decreased, whereas the circumferential strain of the pipe increased. The research results provide a theoretical basis for the prediction of the safety performance of concrete pipes.